THE IMPACT OF INTEGRATING JOYFUL LEARNING PRINCIPLES IN TEAM GAMES TOURNAMENTS ON ELEMENTARY SCHOOL STUDENTS' UNDERSTANDING OF JAVANESE LITERACY CONCEPTS - Much Arsyad Fardani; Dwiana Asih Wiranti; Lintang Kironoratri; Ika Ari Pratiwi (Program Studi PGSD Universitas Flores, 2026)
The background of this study focuses on the low understanding of the Javanese script caused by a monotonous and uninteresting learning approach. This study aims to identify the effectiveness of joyful learning in increasing students’ interest and knowledge of the Javanese script. This study was conducted at SD 1 Padurenan, focusing on fourth-grade students. The method used is a quantitative approach with a one-group pretest-posttest design, involving 17 students as the sample. Data were collected through written tests, interviews, and documentation. The study showed a significant increase in understanding of Javanese script after implementing joyful learning, with an average pretest score of 50 and a posttest score of 82.49. The N-Gain test yielded an average score of 0.6564, indicating a fairly substantial increase. The conclusion of this study shows that applying the principle of joyful learning effectively improves students’ understanding of Javanese script concepts, with implications for the importance of using innovative approaches to learning. The joyful learning principle was applied in this study through the use of the Teams Games Tournament learning model, Javanese script snakes-and-ladders learning media, and student feedback during the learning process.